Decrease in dendritic cells in endomyocardial biopsies of human dilated cardiomyopathy - Pistulli, Rudin; König, Sebastian; Drobnik, Stefanie; Kretzschmar, Daniel; Rohm, Ilonka; Lichtenauer, Michael; Fritzenwanger, Michael; Mall, Gerhard; Mall, Gita; Figulla, Hans-Reiner; Yilmaz, Atilla (European journal of heart failure, 2013)
Aims Dendritic cells (DCs) are sentinels of the immune system—their role in myocardial disease is unknown as yet. We investigated their myocardial presence in human dilated cardiomyopathy (DCM). Methods and results Endomyocardial biopsies from 72 patients with DCM (EF ∼30%), as well as myocardial specimens from 18 suicide or accident victims were immunohistochemically analysed for myeloid and plasmacytoid DCs, antigen-presenting cells (APCs), and other leucocytes; also tissue fibrosis and apoptosis were histologically quantified. The myocardial viral genome was identified through polymerase chain reaction, and patients underwent clinical follow-up in 3-6 months. We found myocardial DCs of all examined subtypes and maturation stages (fascin, CD11c, CD209, CD83, and CD304), as well as markers for APCs (HLA-DR and CD40) and T-cell activation (CD69) to be significantly decreased in DCM compared with controls. In contrast, regulatory T cells (the GITR epitope), apoptosis (by TUNEL reaction and immunostaining with BCL-2), and a DC chemokine receptor (CCR7) were overexpressed, while no significant differences were observed for macrophages (CD68). Immature myeloid and plasmacytoid DCs strongly correlated with endothelial progenitor cells (CD34), which were similarly reduced in DCM, and inversely correlated with fibrosis. Myeloid DCs were especially reduced in virus-positive biopsies, and their numbers correlated with positive change in EF (ΔEF) at follow-up. Conclusion Myocardial DCs are reduced in heart biopsies of symptomatic DCM patients. Such a reduction correlates with an unfavourable short-term outcome in terms of EF, and could result from myocardial tissue damage, cellular death, and insufficient vascularization in chronic heart failure.
First published: 27 January 2014
Gesehen am 10.01.2022